Impact of chloride grinding aid with modified fly ash using topdown nanotechnology on grinding performance. (28th February 2019) - Krishnaraj, L.; Ravichandran, P.T.
Graphical abstract: Highlights: The particles ball milled into ultrafine particles to increase specific surface area. Due to particle size reduction, the particles physical and strength properties improved. The environmental impacts decreased due to ultra fine fly ash usage increased. The Usege of Grinding aids were improves the particle size reduction, the grind ability, and reduce the energy consumption. Abstract: The influence of Grinding Aid (GA) and Grinding Performance (GP) on Raw Fly Ash (RFA) have been analyzed by solid state route to obtain Chloride based Ground Fly Ash (CGFA). Particle size distributions of RFA and CGFA are studied and GP optimization occurred at 120 min. Crystal structures are examined by X-ray Diffraction (XRD) and found to be multiphasic. Crystallite size and microstrain measured using Williamson-Hall plot (from XRD pattern) reveal that reduction in size and lattice gets strained. Microstructure obtained by Scanning Electron Microscope (SEM) shows <5 μm grain size with a spherical shape. Normal consistency found to be increased for both RFA and CGFA when compared to a control sample, whereas setting time is getting increased for RFA and decreased for CGFA. In addition, optimized compressive strength of RFA (15%) and CGFA (45%) blended cement composite mortar shows the higher strength of 6% and 7% respectively. The ball mill grinding process using chloride based grinding aids can be adopted at high volume replacement of fly ash in cement manufactory.